Theorical model for identify social: the housing co-operatives in Setúbal case study - Simões, José; SARDINHA, BOGUSLAWA MARIA BARSZCZAK; Carvalho, Luísa Margarida Cagica (Ekonomsko-poslovna fakulteta, Inštitutza podjetništvo in management malih podjetij, 2005)
Social innovation is a fundamental issue of social entrepreneurship. Private and public organizations and civil society could organize themselves to solve their needs and cooperative sector has a particular role in this area. Sometimes, civil society creates associations to solve their particular problems, and their action has a large scope in social areas. The aim of this paper is to show a theoretical model with a set of qualitative indicators applied to identify social entrepreneurship. In order, to test this theoretical methodology, we would like to apply it to the cooperative sector as a case study. This case study has to do with House Cooperatives in Setúbal, Portugal. Based on the experience and in the analysis of this case study, after evaluating it, we would like to consider the possibility of applying the current model to future situations elsewhere.
Keywords: Social entrepreneurship; Social Innovation; Evaluation; Social